Surviving Treblinka - Samuel Willenberg ; edited by Wladyslaw T. Bartoszewski ; translation by Naftali Greenwood. (Basil Blackwell in association with the Institute for Polish-Jewish Studies, 1989)
Translation of: Mered bi-Treblinkah, which was translated from the Polish manuscript.Includes index.